2014
DOI: 10.1111/j.1532-950x.2014.12165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Intervertebral Disk Spacer on Stiffness After Monocortical Screw/Polymethylmethacrylate Fixation in Simulated and Cadaveric Canine Cervical Vertebral Columns

Abstract: Objective: To determine the biomechanical effect of an intervertebral spacer on construct stiffness in a PVC model and cadaveric canine cervical vertebral columns stabilized with monocortical screws/polymethylmethacrylate (PMMA).Study Design: Biomechanical study.Sample population: PVC pipe; cadaveric canine vertebral columns Methods: PVC model -PVC pipe was used to create a gap model mimicking vertebral endplate orientation and disk space width of large-breed canine cervical vertebrae; 6 models had a 4-mm gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(44 citation statements)
references
References 32 publications
0
39
1
3
Order By: Relevance
“…This device has previously been used in conjunction with String‐of‐Pearl plates to achieve cervical distraction‐stabilization in dogs . The rationale for using it in combination with the screw‐rod system was that in addition to facilitating fusion, it will provide effective load sharing and decrease the risk of fatigue and subsequent implant failure . To introduce the distraction bolt into the L7‐S1 intervertebral space in vivo, the cauda equina is retracted using a long, narrow instrument…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This device has previously been used in conjunction with String‐of‐Pearl plates to achieve cervical distraction‐stabilization in dogs . The rationale for using it in combination with the screw‐rod system was that in addition to facilitating fusion, it will provide effective load sharing and decrease the risk of fatigue and subsequent implant failure . To introduce the distraction bolt into the L7‐S1 intervertebral space in vivo, the cauda equina is retracted using a long, narrow instrument…”
Section: Discussionmentioning
confidence: 99%
“…39 The rationale for using it in combination with the screw-rod system was that in addition to facilitating fusion, it will provide effective load sharing and decrease the risk of fatigue and subsequent implant failure. 26 To introduce the distraction bolt into the L7-S1 intervertebral space in vivo, the cauda equina is retracted using a long, narrow instrument. 40 Limitations: As with any cadaveric experiment, this study has a number of limitations that should be considered when interpreting the data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various distraction‐stabilization methods for treatment of canine cervical spondylomyelopathy have been described clinically, with a few having been assessed biomechanically . It has been sufficiently demonstrated that bicortical implants are not safe to use in the canine cervical spine and investigation has shifted to monocortical fixations such as monocortical screws/polymethylmethacrylate (PMMA) and locking plates .…”
Section: Introductionmentioning
confidence: 99%